Patterns Of Supplier Learning: Case Studies In The Malaysian Automotive Industry - Abdul Kadir, Kadzrina; On, Kit Tam; Ali, Hassan (Asian Academy of Management (AAM), 2011)
Supplier development programs support the development of a supplier's capabilities, usually with the assistance of a buyer. In an industrial environment that lacks homegrown technology, it is of interest to explore precisely how suppliers learn and increase their capabilities. There are also questions regarding how the buyer impacts this learning process, specifically with respect to dependent suppliers for which major buyers account for more than 20% of sales. It is claimed that support from buyers for supplier training has been deficient. Thus, there is a need to identify the types of training that suppliers themselves prefer. The objective of this study is therefore to examine the patterns of learning for dependent suppliers in the Malaysian automotive industry by exploring how suppliers learn best and defining the role of buyers in providing assistance. This study presents a model based on empirical findings and discusses the implications of the findings.